You need a thick skin in this game: Journalists' attitudes to resilience training as a strategy for combatting online violence. Issue 1 (1st June 2020) - Martin, Fiona R.; Murrell, Colleen
In recent years, resilience training has been recommended as a way to protect news workers from the impact of reporting on traumatic events. However, do journalists see it as a useful tool in dealing with online abuse and harassment? This article explores Australian journalists' conceptions of resilience training, via a thematic analysis of interviews, and their concerns about its effectiveness in addressing digital violence. The study adopts an ethics of care framework for understanding the uses of resilience training in journalism education for increasing dialogic interaction with audiences. It finds that while some journalists understand resilience training's relationship to positive mental health, the majority are not clear about its potential and how it might be taught. Our analysis also reveals normative beliefs about journalists' need to develop 'a thick skin' against interpersonal and coordinated violence online. Overall, the article raises questions about how journalists might be better oriented to not only self-care but also collective care.